Uniting hearts and lands: advancing conservation and restoration across the Yellowstone to Yukon region - Hilty, Jodi A.; Chester, Charles C.; Wright, Pamela A.; Zenkewich, Kelly (Frontiers in Conservation Science, 2024)
In view of the escalating anthropogenic impacts of climate change, habitat loss, and fragmentation, a broad consensus within the science community has identified large landscape conservation as critical to the future of nature and humanity. Recent commitments made at a global level offer an unprecedented opportunity for the conservation of biodiversity, particularly inasmuch as Canadian and US policies are aligned, ambitious, and clearly focused on ensuring that conservation work respects and supports the rights of Indigenous Peoples.These commitments align with and support the Yellowstone to Yukon (Y2Y) mission of connecting and protecting the 2,100-mile-long Yellowstone to Yukon region for people and nature to thrive, with the predominant approach of working with local communities and Indigenous Peoples to advance enduring conservation. Since the inception of the vision in 1993, significant progress has been made as indicated by the expansion of protected areas by more than 80 percent, the recovery of some species such as grizzly bears and wolves, and the ecological restoration of key lands across the region. While 25 percent of the Yellowstone to Yukon region is already managed or co-managed by Indigenous Peoples, today Indigenous Peoples are increasingly asserting their leadership and driving forward new restoration and conservation. New Indigenous-led conservation brings critical energy and visions that advance the Y2Y mission and arguably is a model for other parts of the world committed to achieving the 2030 UN Global Biodiversity Framework.